Dendritic cells and natural killer cells: The road to a successful oncolytic virotherapy - Ghasemi, Matin; Abbasi, Laleh; Ghanbari Naeini, Leila; Kokabian, Pajman; Nameh Goshay Fard, Najmeh; Givtaj, Nozar (Frontiers in Immunology, 2023)
Every type of cancer tissue is theoretically more vulnerable to viral infection. This natural proclivity has been harnessed as a new anti-cancer therapy by employing oncolytic viruses (OVs) to selectively infect and destroy cancer cells while providing little or no harm with no toxicity to the host. Whereas the primary oncolytic capabilities of OVs initially sparked the greatest concern, the predominant focus of research is on the association between OVs and the host immune system. Numerous OVs are potent causal agents of class I MHC pathway-related chemicals, enabling early tumor/viral immune recognition and cytokine-mediated response. The modified OVs have been studied for their ability to bind to dendritic cells (DCs) by expressing growth factors, chemokines, cytokines, and defensins inside the viral genome. OVs, like reovirus, can directly infect DCs, causing them to release chemokines and cytokines that attract and excite natural killer (NK) cells. In addition, OVs can directly alter cancer cells’ sensitivity to NK by altering the expression levels of NK cell activators and inhibitors on cancerous cells. Therefore, NK cells and DCs in modulating the therapeutic response should be considered when developing and improving future OV-based therapeutics, whether modified to express transgenes or used in combination with other drugs/immunotherapies. Concerning the close relationship between NK cells and DCs in the potential of OVs to kill tumor cells, we explore how DCs and NK cells in tumor microenvironment affect oncolytic virotherapy and summarize additional information about the interaction mentioned above in detail in this work.